ANALYSIS OF FACTORS AFFECTING THE REMOVAL OF VILLAGE BUMDES MANAGEMENT DILOATO - asna karim; darman darman; samin latif (Journal of Economic, Business, and Administration (JEBA), 2023)
The purpose of the study was to determine the factors that influence the resignation of the BUMDes management in Diloato Village every year. The research method used in this research is descriptive research with a qualitative approach. Data collection techniques used in this study were observation, in-depth interviews (indept interviews) and documentation. Data analysis techniques used in qualitative research include data collection, data reduction, analysis and presentation of data and verification or drawing conclusions. The results of the research are (1) boredom with a long working period, accompanied by dissatisfaction with work, an uncomfortable work environment, disharmony between administrators. (2) The level of education is not the main factor in the resignation of the management, but rather the lack of government support to synergize the skills with the education level of the administrators. (3) The very small salary is a factor that causes the resignation of the Diloato Village BUMDes management.